Hands-On Financial Trading with Python : A practical guide to using Zipline and other Python libraries for backtesting trading strategies /: A practical guide to using Zipline and other Python libraries for backtesting trading strategies. (2021) - Pik, Jiri; Ghosh, Sourav
No abstract available